UPAYA MENINGKATKAN KOMPETENSI NEGOSIASI MELALUI MODEL PEMBELAJARAN ACTION LEARNING - NAILUL HISAN (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2022)
Action learning is one form of implementation of the Ministry of Finance's Corporate University. Action learning activities are implemented after the completion of structured learning. The purpose of this study is know the opinion of participants about action learning activities. The types of action learning activities in PJJ Effective Negotiation Skills are summarizing negotiation books, sharing negotiation knowledge with colleagues, or negotiation practices in the workplace. The research method used qualitative research whose data is obtained from action learning activity reports. The data is collected from the PJJ Effective Negotiation Skills action learning report organized by the Financial Education and Training Center Denpasar 2022. The results showed that participants felt the benefits of action learning activities. From the participants' reports, we obtained information that action learning was able to increase participants' knowledge about negotiations, increase participants' ability to prepare for negotiations, increase participants' readiness to face the different characters of negotiating partners and increase confidence in negotiating. In addition, during the practice of negotiating with partners, participants have also been able to convince their negotiating partners. ABSTRAKAction learning merupakan salah satu bentuk implementasi Kementerian Keuangan Corporate Universiy. Kegiatan action learning dilaksanakan setelah selesainya pembelajaran terstruktur. Penelitian ini bertujuan untuk mengetahui pendapat peserta mengenai kegiatan action learning. Jenis kegiatan action learning pada PJJ Effective Negotiation Skills adalah merangkum buku negosiasi, melakukan knowledge sharing negosiasi kepada rekan kerja, atau melakukan praktik negosiasi di tempat kerja. Metode penelitian yang digunakan adalah penelitian kualitatif yang datanya diperoleh dari laporan kegiatan action learning. Data yang dikumpulkan adalah laproan action learning PJJ Effective Negotiation Skills yang diselenggarakan oleh Balai Diklat Keuangan Denpasar 2022. Hasil penelitian menunjukkan bahwa peserta merasakan manfaat kegiatan action learning. Dari laporan peserta, diperoleh informasi bahwa action learning mampu menambah pengetahuan peserta mengenai negosiasi, meningkatkan kemampuan peserta dalam melakukan persiapan negosiasi, meningkatkan kesiapan peserta menghadapi keragaman karakter mitra negosiasi dan menambah kepercayaan diri dalam melakukan negosiasi. Selain itu saat praktek negosiasi dengan mitra kerja peserta juga telah mampu meyakinkan lawan negosiasinya.